UPAYA PENINGKATAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI KEGIATAN MENGGUNTING DAN MENEMPEL BAGI ANAK KELOMPOK B TK PELITA HATI KUARO TAHUN PELAJARAN 2020/2021 - Ernawati Ernawati (Program Studi S1 PG-PAUD, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Satya Wacana, 2023)
Based on observations made at Pelita Hati Kindergarten, it was found that he had not been able to coordinate his fine motor skills, be it holding stationery, matching cutting and sticking well. Sometimes children feel quickly saturated because they are unable to do the tasks given by Class Action Research carried out with the aim of achieving the development of the child's fine motor aspects through matching activities, making cattle and sheep pens and making miniature farms. The subjects in the study were children in group B with a total of 5 children. Which lasts for 3 cycles. The results of Cycle I, Cycle II and Cycle III in improving children's fine motor skills through cutting and sticking activities, it can be said that the abilities of 5 children, who develop according to expectations do not exist, in Cycle I as many as 1 child or by 20% while in cycle II are as many as 2 children or by 40% and in cycle III become 3 children or as much as 60% and 1 child develops very well or by 20% so that the child those who were able to cut and stick (develop as expected) experienced an increase of 3 children or by 60%. And for excellent Developing Ability that in cycle I does not exist in cycle II to 1 child or up 20%